2016
DOI: 10.2147/ott.s91848
|View full text |Cite
|
Sign up to set email alerts
|

The clinical pathological characteristics and prognosis of FGFR1 gene amplification in non-small-cell lung cancer: a meta-analysis

Abstract: FGFR1 amplification is recognized as a novel therapy target for non-small-cell lung cancer (NSCLC), especially in squamous cell carcinoma (SCC). However, the association between FGFR1 amplification and the clinicopathological characteristics of NSCLC remains controversial. We performed a meta-analysis of 17 eligible studies to examine the correlation between FGFR1 gene amplification and clinicopathological characteristics. FGFR1 amplification was closely related to these clinicopathological features, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Apoptosis assay. H1975 (1x10 6 ) and H358 (1x10 6 ) cells were treated with lenvatinib (40 ng/ml), TGF-β1 (40 ng/ml), dexamethasone (20 µM) or combined treatment for 12 h at 37˚C. The cells were incubated with PBS and the apoptosis of the suspended cells was analyzed by flow cytometry.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis assay. H1975 (1x10 6 ) and H358 (1x10 6 ) cells were treated with lenvatinib (40 ng/ml), TGF-β1 (40 ng/ml), dexamethasone (20 µM) or combined treatment for 12 h at 37˚C. The cells were incubated with PBS and the apoptosis of the suspended cells was analyzed by flow cytometry.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…NSCLC, including squamous cell carcinoma, large cell carcinoma and adenocarcinoma, accounts for >80% of all lung cancer cases (3)(4)(5). Although studies have provided therapeutic improvements for NSCLC, the poor survival rate (overall 5-year survival rate, <15%) of patients with NSCLC is primarily attributed to critical clinical problems, including tumor cell diffusion and metastasis (4,6,7). Migration and invasion of NSCLC is the primary cause of the poor survival rate during treatment and recurrence for patients with NSCLC (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that tumorigenesis is a complex process with a wide spectrum of genetic alterations [6]. These genes typically exhibit aberrant expression patterns and have clinical significance in cancer diagnosis and prognosis [7]. Currently, some molecules have been recognized as diagnostic and prognostic biomarkers in oligodendroglial tumor.…”
Section: Introductionmentioning
confidence: 99%
“…A previous pathological study has suggested that NSCLC accounts for ~80% of all lung cancer cases and classified adenocarcinoma, large cell carcinoma and squamous cell carcinoma as common types of NSCLC (4). A number of therapeutic strategies, such as immunotherapy, gene therapy, radiotherapy and chemotherapy, have been widely applied in clinical settings for the treatment of NSCLC (5-7); however, poor survival rates of patients with NSCLC have continued (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%